2015
DOI: 10.1039/c4cp05550k
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of room temperature ionic liquids: from polarizable to coarse-grained force fields

Abstract: Room temperature ionic liquids (RTILs) are solvent with unusual properties, which are difficult to characterize experimentally because of their intrinsic complexity (large number of atoms, strong Coulomb interactions). Molecular simulations have therefore been essential in our understanding of these systems. Depending on the target property and on the necessity to account for fine details of the molecular structure of the ions, a large range of simulation techniques are available. Here I focus on classical mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(184 citation statements)
references
References 123 publications
(134 reference statements)
7
176
0
Order By: Relevance
“…2). It is known that standard atomistic force fields neglecting polarization effects quantitatively deviate from experimental findings related to the mean-square displacement of species 118,119 . However, here we are able to compare and discuss the results for the different species in a qualitative way.…”
Section: Mass Densities and Diffusion Coefficientsmentioning
confidence: 99%
“…2). It is known that standard atomistic force fields neglecting polarization effects quantitatively deviate from experimental findings related to the mean-square displacement of species 118,119 . However, here we are able to compare and discuss the results for the different species in a qualitative way.…”
Section: Mass Densities and Diffusion Coefficientsmentioning
confidence: 99%
“…by theoretical/molecular simulation methods [12][13][14][15][16][17][18][19][20] and several predictive models have been proposed. 11,[21][22][23][24] Currently it is well accepted that ILs are highly structured fluids in which the ion pairs arrange themselves into polar and non-polar domains.…”
Section: Introductionmentioning
confidence: 99%
“…Simply considering e = 1 in the Coulomb term would neglect the dynamic (induction) polarization effects, whereas including the static dielectric constant of the solvent would roughly amount to counting twice the static interactions. Recent theoretical works [46,47] have demonstrated that the electronic polarization in ionic liquids can be accounted for by scaling the Coulomb interactions by a factor 1-1/e el , where e el is the (fast/optical) electronic dielectric constant of the medium, which can be determined by experimental measures of the refractive index as e el = n 2 . [48] From the refractive indices of 1.3979 for DOL and 1.4307 for TEGDME at room temperature, [49] we obtain e el values of 1.18 for DOL and 1.19 for TEGDME.…”
Section: Parameterization Of the Solventsmentioning
confidence: 99%